Effect of Iron Deficiency Anemia on HbA1c Levels in Patients of Diabetes Mellitus with Controlled Plasma Glucose Levels - Smita N. Vasava; Roshni Sadaria; Tejas Shah (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Hemoglobin A1C (HbA1c) is an indicator of patient’s glycemic status over the previous 3months. HbA1C levels increase in presence of Iron deficiency anemia.Aim: To analyze the effect of iron deficiency anemia on HbA1c levels in patients of diabetes mellitus withcontrolled plasma glucose levels.Material and Methods: In the present study, total 50 patient of diabetes mellitus with iron deficiencyanemia with controlled plasma glucose levels were taken as a cases and 50 iron-sufficient non-anemichealthy individuals were taken as a controls. Medical history was taken from all participant and data ofHbA1c, ferritin, FBS, hemoglobin, peripheral smear examination, red cell indices were collected fromlaboratory. Statistical analysis was carried out by student’s t-test, Chi-square test, and Pearson’s coefficientof regression.Results: HbA1C level (6.90 ± 0.81%) were increased in iron-deficient individuals as compared to controls.In females, HbA1C (7.08 ± 0.78%) were more elevated than males. When classified on the basis of FBS,HbA1C was elevated more in subjects having FBS between 100-126 mg/dl (7.31 ± 1.52%) compared to thethose with normal FBS (<100 mg/dl).Conclusion: A positive correlation found between iron deficiency anemia and increased HbA1C levels,especially in the controlled diabetic women and individuals having FBS between 100-126 mg/dl. Therefore,presence of iron deficiency anemia should be checked before altering the treatment regimen of diabetesmellitus patient.